Transition pathways and vision-to-action in the Agroecological Living Landscapes (ALLs) in Kenya - Fuchs, Lisa; Adoyo, Beatrice; Levi, Orero; Korir, Hezekiah; Sakha, Michael; Anyango, Edith; Ongus, Emily; Van Dien, Cannell; Kipkoror, Langat; Abondi, Victoria; Ntinyari, Winnie; Bolo, Peter Omondi; et al. (2023)
This report documents activities implemented under Work Package 1 (WP1) in the CGIAR Agroecology Initiative (AE-I) in Kenya. WP1 focuses on establishment and engagement of the Agroecological Living Landscapes (ALLs), as well as on-farm agroecological innovations. Specifically, the report covers the visioning and vision-to-action engagement in the two Kenyan ALLs in Kiambu and Makueni, respectively. A separate report details the on-farm innovation process and results in Kenya.